Perícia contábil judicial: um estudo acerca das sentenças prolatadas na cidade de São Paulo no primeiro semestre de 2015 - Silvestrin, Priscilla Silva (2015)
The Accounting Science's mission is to assist decision making. The accounting reports are the instrument by which the water meter provides information that will serve as a resource to meet this purpose. Judicial accounting expertise serve a specific external user, which is the judge who has the task of resolving social conflicts installed with justice and equity. The main objective of this research is to analyze the performance of judicial accounting expertise in Sao Paulo in the first half of 2015. The study used based on the data made public by the São Paulo State Court of Justice relating to judicial decisions handed down in the period and procedural movements using quantitative methods. In addition to quantitative methodology, the paper presents literature, intended to clarify and bring concepts relating to Accounting and the science of law, which includes forensic accounting expert. From the collected data it is possible to realize the increase of judicial decisions in time and that the ratio between the number of sentences and those who have the term forensic accounting is on average 0.55% (zero point fifty-five percent). In decisions where there is mention of the term forensic accounting, in 46% (forty-six percent) of them, the judge denies the realization of forensic accounting, 23% (twenty three percent) the judge believes it would be the case achievement of expertise, but these were not required and 31% (thirty-one percent) was the approval of the accounting expert evidence. Of deferred and unrealized sentences, 11% (eleven percent) of cases, given up parts of the production of evidence, in 24% (twenty-four percent) the parties have not submitted enough documents to carry out the expertise and 65 % (sixty five percent), the parties failed to collect fees. The skills deferred and performed, 88% (eighty eight percent) there was no assistant coach, while in 12% (twelve percent) decisions there. From the decisions where there was contradictory regarding the accounting demonstration, it was found that the appointed experts, 12% (twelve percent) do not have active registration with the Regional Accounting Council and 82% (eighty two percent) did not It has registered curriculum in the Lattes platform